Multihalle by Frei Otto. A cover generated by compression, as a model. Mannheim, 1974-1975 - Molina León, Fernando M. (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
Frei Otto is well known for his tractioned membrane architecture. Perhaps that is why his work with elements working in compression has been dismissed. The Mannheim´s Multihalle is a pavilion of great dimension that stands out for its structural behaviour: with highly optimized resources, savies such great lights. At first, it was designed for a temporary use, but until now the pavilion has been standing for 43 years, which highlights its great value. Without the technology of today the calculation of the Multihalle was quite a feat. The pavilion served at the same time as a test model and a building. The daring of the german architect when making the simplest complex cover in the world inspired this article. We describe through models the formalization process of its lattice.